2017
DOI: 10.1016/j.jcot.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with venous thromboembolism prophylaxis (VTE)

Abstract: Venous thromboembolic disease (VTE) comprises pulmonary embolism (PE) and deep vein thrombosis (DVT), and causes morbidity and mortality, particularly in trauma and orthopaedic patients. Prevalence of 0.9% and 1.2% respectively are reported, with mortality rates up to 13.8%. Chemical thromboprophylactic agents including low molecular weight heparin (LMWH) are considered cost effective in reducing VTE risk. Evidence for anti-platelets including Aspirin for VTE prophylaxis is less compelling and is not supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…18 In terms of VTE chemoprophylaxis, adherence with medication orders has been reported by pharmacy records as well as patient report. 19,20 Chemoprophylaxis is often the most straightforward modality to monitor in clinical practice. Because of the strict regulations surrounding administration of medications in the hospital setting and meticulous documentation of dosing and timing, identifying missed doses of medications is rather straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…18 In terms of VTE chemoprophylaxis, adherence with medication orders has been reported by pharmacy records as well as patient report. 19,20 Chemoprophylaxis is often the most straightforward modality to monitor in clinical practice. Because of the strict regulations surrounding administration of medications in the hospital setting and meticulous documentation of dosing and timing, identifying missed doses of medications is rather straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] There have been no published studies comparing non-adherence to once-daily aspirin versus once-daily enoxaparin when used for VTE prophylaxis following THA or TKA. Previously published studies have either compared twice-daily aspirin to LMWH for orthopaedic trauma patients 9,10 or DOACs to LMWH following THA or TKA. 5,11 The reasons underlying non-adherence have also been poorly reported, with the exception of one study which found that the most common reasons for non-adherence to extended aspirin prophylaxis were a lack of patient belief that it was required for 6 weeks, uncertainty regarding the required prophylaxis duration and conflicting advice given by practitioners other than the treating surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Deep vein thrombosis (DVT) is a major complication of lower limb fractures 1 that may incur in death risk, such as for leading to pulmonary thromboembolism. 2 DVT is directly related to high-energy trauma.…”
Section: Introductionmentioning
confidence: 99%